(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper investigates the pivotal role of commercial banks in promoting Corporate Social Responsibility (CSR) within Haryana. Given the recent emphasis on CSR in businesses globally, the importance of incorporating these practices in the banking sector cannot be overstated. This study uses qualitative and quantitative methods to assess the impact of banks’ CSR activities in Haryana, evaluating various initiatives and their socio-economic implications